Assessing Climate Change Worry among Undergraduate Nursing Students in Sindh, Pakistan: A Cross-sectional Study - Hussain, Mudasir; Khowaja, Shaneela; Channar, Hussan Banno; Ali, Nadir; Soomro, Fatima; Abbasi, Waqar Ahmed; Kalhoro, Faique Ali; Hafeez, Mairaj (Indus Journal of Bioscience Research, 2025)
Background: Climate change is increasingly recognized as a significant threat to mental health globally. This study investigates the prevalence and nature of climate-related worry among undergraduate nursing students in Sindh, Pakistan, and explores differences between public and private institutions. Methods: A cross-sectional survey was conducted from March to May 2025 across public and private nursing colleges in Sindh. A total of 291 students participated, completing a 10-item Climate Change Worry Scale (CCWS) alongside demographic questions. Descriptive statistics characterized the sample and mean CCWS scores. A one-sample t-test determined whether the mean worry score was significantly above the neutral midpoint (score = 3.0). Mann–Whitney U tests compared item-level responses between public and private college students. Results: Participants (75.3% male; 72.5% aged 21–30; 60.1% rural; 78% Sindhi) exhibited a mean CCWS score of 3.25 (SD = 0.65), significantly above neutral (t(290) = 5.24, p < 0.001). Many frequently worried about the future (54.6%), loved ones (62.1%), and felt “paralyzed” by their concern (48.1%). Public vs. private institution comparisons revealed significant differences in worry intensity and proactive engagement for four items: self-comparative worry (p = 0.001); future-oriented anxiety (p = 0.006); personal impact (p = 0.025); and suggesting solutions (p = 0.004). Conclusions: Climate-related worry is significantly present among nursing students in Sindh, particularly when considering emotional impact and engagement. Differences between institutional groups suggest the influence of educational or contextual factors. Results underscore the need to integrate climate-related mental health content into nursing education and to develop longitudinal and interventional research to support adaptive coping and resilience in future healthcare professionals.